Framework Based on Building Information Modelling for Information Management by Linking Construction Documents to Design Objects - HeeSung Cha; DongGun Lee (Journal of Asian Architecture and Building Engineering, 2018)
Most construction project information is stored in unstructured documents, despite its increasing scale and complexity. Owing to ineffective management of construction information, the construction industry is significantly less productive than other industries. Although building information modelling (BIM) is widely employed in the industry, it is difficult to model the project execution phase data owing to its high level of detail. Therefore, this study proposes a framework based on BIM that enables the storing and searching of construction project data through an effective linkage of documents with 3D design objects. The information breakdown structure and spatial breakdown structure, which are the media for integrating construction data with information technology, have been established through the identification and classification of information from unstructured documents from construction sites. The efficiency of the proposed framework in linking documents with 3D objects was validated through a pilot test project and industry survey. The proposed methodology is expected to assist in resolving issues in information management, including enhanced communication, accumulation of know-how, and minimization of disputes, if the utility of the methodology is improved by continuously discovering the best practices at the industrial or organizational level through its extended application.